Lipophilic marine toxins discovered in the Bohai Sea using high performance liquid chromatography coupled with tandem mass spectrometry. (September 2017) - Liu, Yang; Yu, Ren-Cheng; Kong, Fan-Zhou; Li, Chen; Dai, Li; Chen, Zhen-Fan; Zhou, Ming-Jiang
Abstract: Some dinoflagellates can produce lipophilic marine toxins, which pose potent threats to seafood consumers. In the Bohai Sea, an important semi-closed inland sea with intensive mariculture industry in China, there is little knowledge concerning lipophilic marine toxins and their potential threats. In this study, net-concentrated phytoplankton samples were periodically collected from 5 typical mariculture zones around the Bohai Sea, including Laishan (LS), Laizhou (LZ), Hangu (HG), Qinhuangdao (QHD) and Huludao (HLD) in 2013 and 2014, and a method using high performance liquid chromatography (HPLC) coupled with a Q-Trap mass spectrometer was applied to analyze seven representative lipophilic marine toxins, including okadaic acid (OA), dinophysistoxin-1 (DTX1), pectenotoxin-2 (PTX2), yessotoxin (YTX), azaspiracid-1 (AZA1), gymnodimine (GYM), and 13-desmethyl spirolide C (desMeC). The method had high sensitivity and repeatability, and exhibited satisfactory recoveries for most of the lipophilic marine toxins (92.1–108%) except for AZA1 (65.8–68.9%). Nearly all the lipophilic marine toxins could be detected in phytoplankton samples from the Bohai Sea. OA, DTX1 and PTX2 were predominant components and present in most of the phytoplankton samples. The maximum content of lipophilic marine toxin in phytoplankton samples concentrated from seawater (OA 464 pg L −1 ; DTX1 783 pg L −1 ; YTX 86.6 pg L −1 ; desMeC 15.6 pg L −1 ; PTX2 1.11 × 10 3 pg L −1 ) appeared in June 2014. Based on toxins present in phytoplankton samples, it is implied that seafood in the Bohai Sea is more likely to be contaminated by OA group and PTX group toxins, and spring is the high-risk season for toxin contamination. Highlights: Net-concentrated phytoplankton samples were collected from 5 sites around Bohai Sea. An HPLC-MS/MS method was used to analyze seven typical lipophilic marine toxins. Most toxins were detected and OA/PTX group toxins were predominant components. The maximum values of lipophilic marine toxin content appeared in June. The findings offer a sound basis for monitoring lipophilic marine toxins in Bohai Sea.